Role of Alphasatellite in Begomoviral Disease Complex: Begomoviral Disease and Alphasatellite (Biological Sciences - PJSIR, 2016)
A circular single stranded satellite, called as alphasatellite (initially identified as DNA-1), wascharacterised and confirmed to be associated with the Geminivirus begomovirus-betasatellite complexes.Alphasatellites are single stranded DNA (ssDNA) components, frequently accompanying with monopartitebegomovirus or some time with bipartite begomovirus and/or betasatellite complex. The genome ofalphasatellite DNAs are nearly half size of its helper virus genome and have no similarity with it. Furthermore,their function in begomovirus-betasatellite complex is still unclear. Recent advances in application ofmolecular tools helped in finding new viruses and allied satellite components that further help in advancingour understanding o f this satellite DNA and this evolution